2013
DOI: 10.1097/mph.0b013e318284127d
|View full text |Cite
|
Sign up to set email alerts
|

Educational Achievement, Employment, Smoking, Marital, and Insurance Statuses in Long-term Survivors of Childhood Malignant Solid Tumors

Abstract: Our results have drawn a more marked picture with lower educational achievement and marital rates when compared with the results of large survivorship studies conducted in developed countries. However, they can be interpreted as intriguing when limited resources are taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Educational and vocational disadvantages are also reported in CCS. Although some CCS report greater school satisfaction than controls, CCS generally have lower educational attainment . Likewise, they are less often in high skilled managerial or professional positions, less likely to work full‐time, receive lower incomes than their gender‐matched siblings, and are more likely to be unemployed .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Educational and vocational disadvantages are also reported in CCS. Although some CCS report greater school satisfaction than controls, CCS generally have lower educational attainment . Likewise, they are less often in high skilled managerial or professional positions, less likely to work full‐time, receive lower incomes than their gender‐matched siblings, and are more likely to be unemployed .…”
Section: Resultsmentioning
confidence: 95%
“…Excluded patients with HSCT or CNS tumors Female sex, current lack of intimate relationship and presence of late medical effects independently associated with increased psychological distress (these variables explained 12% of variance) Suppressing negative thoughts and low levels of optimism identified as coping mechanisms associated with worse distress (addition of coping variables explained 50% of variance) Moderate sample size, no comparison population, data collection and analysis appropriate, evidence derived from high quality cohort study, reporting comprehensive, issues with missing data clearly described.6xxWilliams, 2013 Screening for psychological well‐being in childhood cancer survivors: a preliminary assessment of the feasibility of the strength and difficulties questionnaire as a parent‐proxy report Cross‐sectional survey of parents of CCS and adolescents.Mothers of CCS (n = 35; survivor's mean age at dx = 6 yrs (SD 3.7), mean current age = 11 (SD 3.4), mean years post‐therapy = 3.9 (SD 0.76)], plus adolescent survivors (n = 14, age ≥15) 50%, 29%, 21%, and 14% of adolescent survivors reported abnormal emotional symptoms, conduct problems, hyperactivity, and peer relationships problems, respectively. Among parents, 52%, 23%, 48% and 57% report the above 4 problems in their children, respectively. Concordance poor between adolescents and parents (Kappa −0.13 to 0.32, all p > 0.10). Small sample size, convenience sample, mixed parents and adolescent report which was appropriate for developmental age; rates reported separately for each group; Data collection and analysis appropriate, reporting comprehensive.4xWinterling, 2015, Perceptions of School Among Childhood Cancer Survivors: A Comparison With Peers Mixed methods; Cross‐sectional, Quantitative survey and qualitative semi‐structured in‐person interviewsN = 48, CCS from Swedish national cohort of CCS, (current age 12–21, median 5 years post‐therapy, HSCT patients excluded), and N = 47 matched peers. 90% of survivors report high levels of well‐being in school 60% report no difficulties achieving educational goals Survivors more satisfied with school environment compared to peers (92% vs. 46%, p = 0.003) Trends suggest survivors more satisfied with academic performance (71% vs. 53%, p = 0.076) and less satisfied with friends at school (76% vs. 91%) compared to peers Small sample size, strong matched peer comparison group, clear reported findings and analysis appropriate for small sample.4xYağci‐Küpeli, 2013 Educational achievement, employment, smoking, marital, and insurance statuses in long‐term survivors of childhood malignant solid tumors Cross‐sectional survey‐basedCCS in remission for 3+ years, (n = 201, median age at diagnosis 10 (0‐19), median current age 23 (18‐39); compared with population norms 56% and 23% of surv...…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Many studies found that survivors of a CNS tumour achieved a much lower educational level than an external group without a history of childhood cancer or than survivors of other types of childhood cancer . Additional determinants identified across the studies included treatment with radiation therapy (most frequently CRT) and younger age at diagnosis …”
Section: Resultsmentioning
confidence: 99%
“…35 Many studies found that survivors of a CNS tumour achieved a much lower educational level than an external group without a history of childhood cancer or than survivors of other types of childhood cancer. 35,36,[40][41][42][43][44][45] Additional determinants identified across the studies included treatment with radiation therapy (most frequently CRT) and younger age at diagnosis. 12,27,36,[39][40][41]46 Working life Table 2b summarises the findings of 29 studies of the employment status and occupations of childhood cancer survivors.…”
Section: Educational Achievementsmentioning
confidence: 99%
“…Importantly, some of those same risk factors also predict poor psychological health/adjustment and adaptive dysfunction, in part because neurocognitive problems can reflect or exacerbate associated mood, behavioral, social, or adaptive issues. Relative to controls, pediatric cancer survivors are more likely to require special education, are less likely to graduate from high school and college or to marry, and report greater overall distress and decreased quality of life . Neuropsychological services help to identify and potentially ameliorate cognitive and academic deficits and their emotional and behavioral sequelae, which is why neuropsychologists often work within interdisciplinary psychosocial teams with multiple team members, including pediatric psychologists, to assess and support psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%